Inhibition of Influenza Virus Infection by Lentinus edodes Mycelia Extract Through Its Direct Action and Immunopotentiating Activity - Kuroki, Takahiro; Lee, Sangjoon; Hirohama, Mikako; Taku, Tomohiro; Kumakura, Michiko; Haruyama, Takahiro; Nagata, Kyosuke; Kawaguchi, Atsushi (Frontiers in Microbiology, 2018)
Lentinula edodes mycelia solid culture extracts (LEM) contain many bioactive compounds with diverse pharmacological activities such as antitumor, antiviral, and immunopotentiating effects. In this study, we examined the anti-influenza virus activity of LEM in vitro and in vivo. LEM directly inhibited influenza virus growth in vitro at early phases of infection, possibly at the entry process of viral particles to host cells. We also found that the nasal administration of LEM increased the survival rate of infected mice, and this was likely due to the direct action of LEM on the viral growth. The oral administration of LEM showed prolonged median survival time of infected mice. Histological analysis revealed that the moderate bronchiolitis was observed in infected mice by the oral administration with LEM, and the extent of alveolitis was dramatically reduced. The orally LEM-administered mice showed a rapid activation of IFN-β gene expression upon influenza virus infection. These results suggest that the immunopotentiation activity of LEM on type I IFN pathway represses the virus spread to distal alveolar regions from peribronchiolar regions which are primary infection sites in the mouse model. We propose that LEM has anti-influenza virus activities through the direct action on viral growth and stimulatory activity of innate immunity.